2006
DOI: 10.1007/s10549-006-9219-7
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced inactivation of sensory neurons promotes a more aggressive gene expression phenotype in breast cancer cells

Abstract: Capsaicin-induced inactivation of sensory neurons has been reported to enhance metastasis of a murine breast cancer cell line, specifically enhancing myocardial metastases. Here we characterized changes in gene expression patterns in primary tumors which developed in capsaicin-treated vs. control mice. We identified a small cohort of genes (17) which all showed significant decreases in expression levels. All of the identified genes have been linked to cell growth, differentiation, and/or cancer progression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 89 publications
2
59
0
Order By: Relevance
“…Epidemiologic studies suggested a positive association between the incidence of stomach cancer and the consumption of chili pepper-rich diets (7). Capsaicin enhanced the metastasis of murine breast cancer cells by reducing the expression of apoptosis-related genes (8) and induced LNCaP prostate cancer cell proliferation by increasing androgen receptor expression through the activation of ERKs and Akt (9). Thus, clarifying the underlying molecular mechanisms to reveal whether or not capsaicin exerts carcinogenic activities is important.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies suggested a positive association between the incidence of stomach cancer and the consumption of chili pepper-rich diets (7). Capsaicin enhanced the metastasis of murine breast cancer cells by reducing the expression of apoptosis-related genes (8) and induced LNCaP prostate cancer cell proliferation by increasing androgen receptor expression through the activation of ERKs and Akt (9). Thus, clarifying the underlying molecular mechanisms to reveal whether or not capsaicin exerts carcinogenic activities is important.…”
Section: Introductionmentioning
confidence: 99%
“…Hence part of VIP and majority of CGRP in our samples might be originated from infiltrating immune cells. It was previously shown that loss of peptidergic sensory neurons sensitive to capsaicin increases metastasis of breast carcinoma inducing aggressive phenotype and possibly stemness and resistance to treatment [18,20,27]. Although it was not possible to measure peptide levels in normal kidney tissues (not involved with a tumor), comparing kidney samples of different subtypes demonstrated the loss of peptidergic innervation was most obvious in kidney neighboring papillary RCC.…”
Section: Discussionmentioning
confidence: 99%
“…SP is found in both neuronal and extraneuronal cells [16] and we recently demosntrated that SP through neuroimmune modulation decreases breast cancer metastasis and enhances the therapeutic effects of radiotherapy [17]. Recent findings suggest that hydrolysis of SP by NEP produces bioactive fragments which inhibit tumor cell growth [18]. These neuropeptides, particularly CGRP and SP, are also found in capsaicin-sensitive sensory nerve fibers which may act to inhibit cancer metastasis as demonstrated in animal models [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the autocrine secretion of SP promotes the growth and metastases of melanoma. Conversely, we observed that the depletion of SP from sensory nerve endings increased breast cancer metastases (4,5). Furthermore, treatment with SP decreased the growth of melanomas, small-cell lung cancer, colon cancer and prostate cancer (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%